Measurement of the differential cross sections for top quark pair production as a function of kinematic event variables in pp collisions at $\sqrt s$=7 and 8 TeV - CMS collaboration (2311 authors) (2016)
Measurements are reported of the normalized differential cross sections for top quark pair production with respect to four kinematic event variables: the missing transverse energy; the scalar sum of the jet transverse momentum (pT); the scalar sum of the pT of all objects in the event; and the pT of leptonically decaying W bosons from top quark decays. The data sample, collected using the CMS detector at the LHC, consists of 5.0  fb−1 of proton-proton collisions at s=7  TeV and 19.7  fb−1 at s=8  TeV. Top quark pair events containing one electron or muon are selected. The results are presented after correcting for detector effects to allow direct comparison with theoretical predictions. No significant deviations from the predictions of several standard model event simulation generators are observed.